From the Death of God to the Rise of Hitler - Sascha O. Becker; Hans-Joachim Voth (Institute of Labor Economics (IZA), 2023)
Can weakened religiosity lead to the rise of totalitarianism? The Nazi Party set itself up as a political religion, emphasizing redemption, sacrifice, rituals, and communal spirit. This had a major impact on its success: Where the Christian Church only had shallow roots, the Nazis received higher electoral support and saw more party entry. "Shallow Christianity" reflects the geography of medieval Christianization and the strength of pagan practices, which we use as sources of exogenous variation. We also find predictive power at the individual level: Within each municipality, the likelihood of joining the Nazi Party was higher for those with less Christian first names.
Keywords: N13; N14; N44; P16; Z12; Z18; 330; political religion; behavioral political economy; voting; Nazi Party; Protestantism; Shallow Christianity; political religion; Paganism